Application of Bayesian Networks in the recurrence of cancer of breast (International Journal of Geoscience, Engineering and Technology, 2022)
Despite the effectiveness in the treatment of breast cancer when discovered early and the possible cure even when discovered late, patients live with uncertainty in the face of the possibility of recurrence of the disease. Artificial Intelligence tools, used in solving complex problems, can help to identify the probability or not of recurrence and identify the main factors associated with it. Therefore, this work is based on the use of Bayesian Networks, through Netica software, as a tool that calculates the probability of occurrence of an event based on data from the variables related to it, to identify patterns associated with the recurrence rate of the event. breast cancer, from data concerning the type of nodule, grade, menopause, which breast and age of the patients.